2005
DOI: 10.1099/vir.0.80531-0
|View full text |Cite|
|
Sign up to set email alerts
|

Dengue virus-induced apoptosis in hepatic cells is partly mediated by Apo2 ligand/tumour necrosis factor-related apoptosis-inducing ligand

Abstract: Although hepatic injury is reported in cases with dengue haemorrhagic fever and dengue shock syndrome, its mechanism remains poorly understood. Several findings suggest that dengue virus (DEN) induces apoptosis of hepatocytes in vivo. In this work, DEN type 2 (DEN-2) strain NGC was shown to induce apoptosis in the hepatic cell line HepG2, and infection of HepG2 cells was found to induce Apo2 ligand (Apo2L, also known as tumour necrosis factor-related apoptosis-inducing ligand or TRAIL) expression. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…Table 1 lists those genes exhibiting increased expression (≥1.5 fold) in DENV-infected mice compared to the mock control. TNF-␣, TRAIL and Fas mRNA expression increased 5-fold, 3-fold, and 2-fold, respectively; these results are similar to those obtained from in vitro analysis of apoptosis in DENV-infected hepatic cell lines (Limjindaporn et al, 2007;Matsuda et al, 2005;Nagila et al, 2013). The pro-apoptotic profile of infected cells was also evident by the increased expression of Bid, Bax and Bak, as well as members of the caspase proteolytic cascade, Apaf-1, caspases-4 and caspases-14.…”
Section: Apoptotic Gene Expression Profile In Liver Of Denv-infected supporting
confidence: 90%
See 2 more Smart Citations
“…Table 1 lists those genes exhibiting increased expression (≥1.5 fold) in DENV-infected mice compared to the mock control. TNF-␣, TRAIL and Fas mRNA expression increased 5-fold, 3-fold, and 2-fold, respectively; these results are similar to those obtained from in vitro analysis of apoptosis in DENV-infected hepatic cell lines (Limjindaporn et al, 2007;Matsuda et al, 2005;Nagila et al, 2013). The pro-apoptotic profile of infected cells was also evident by the increased expression of Bid, Bax and Bak, as well as members of the caspase proteolytic cascade, Apaf-1, caspases-4 and caspases-14.…”
Section: Apoptotic Gene Expression Profile In Liver Of Denv-infected supporting
confidence: 90%
“…Inhibition of p38 MAPK in HepG2 cells also reduces TNF-␣ production and apoptosis during DENV infection (Nagila et al, 2013). DENV infection induces apoptosis in HepG2 cells partly through the induction of TRAIL (Matsuda et al, 2005). Hepatitis C virus also uses TRAIL to sensitize hepatocytes to apoptosis (Lan et al, 2008).…”
Section: Inhibition Of Erk1/2 Phosphorylation Alters the Expression Omentioning
confidence: 98%
See 1 more Smart Citation
“…Several findings include direct infection of the dengue virus and induction of apoptosis, immune mediated hepatocyte injury by CD4 lymphocyteinduced lysis and cytokine production (Marianneau et al, 1997;Gagnon et al, 1999;Huerre et al, 2001;Matsuda et al, 2005). Unlike conventional viral hepatitis, in dengue infections the level of AST is higher than that of ALT (Kuo et al, 1992).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, recently it was shown that DENV-2 induces apoptosis in hepatoma cells (HepG2) either by infection or partly mediated by Apo2L/TRAIL. Therefore, DENV infection might cause a local cytokine environment in liver tissue that contributes to induction of apoptosis in non infected hepatocytes (Matsuda et al, 2005).…”
Section: Discussionmentioning
confidence: 99%